Observation of B0s → χc1ϕ decay and study of B0 → χc1,2K*0 decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Nuclear physics. B, Particle physics, 2013)
The first observation of the decay Bs0→χc1ϕ and a study of B0→χc1,2K⁎0 decays are presented. The analysis is performed using a dataset, corresponding to an integrated luminosity of 1.0 fb−1, collected by the LHCb experiment in pp collisions at a centre-of-mass energy of 7 TeV. The following ratios of branching fractions are measured:B(Bs0→χc1ϕ)B(Bs0→J/ψϕ)=(18.9±1.8 (stat) ±1.3 (syst) ±0.8(B))×10−2,B(B0→χc1K⁎0)B(B0→J/ψK⁎0)=(19.8±1.1 (stat) ±1.2 (syst) ±0.9(B))×10−2,B(B0→χc2K⁎0)B(B0→χc1K⁎0)=(17.1 ±5.0(stat)±1.7(syst)±1.1(B))×10−2, where the third uncertainty is due to the limited knowledge of the branching fractions of χc→J/ψγ modes.